Accurate and Efficient Characterization of a High Voltage Capacitor by Fitting Single Discharge Experiments With a Simple Circuit Theory - Chang, Po-Yu; Aranganadin, Kaviya; Hsu, Hua-Yi; Lin, Ming-Chieh (IEEE access, 2025)
A capacitor is ideally considered as a pure capacitance, but under practical conditions, it also exhibits some resistive and inductive properties, called equivalent series resistance (ESR) and equivalent series inductance (ESL), respectively. These ESR and ESL characteristics are usually ignored in most cases as a first approximation. For high-power and/or high-frequency applications, especially pulsed systems, designed to achieve an accurate and reliable output, it is important to take these parasitic effects into consideration in circuit designs and operations. Conventionally, two capacitors are used, and two discharge tests are required to obtain the ESR and ESL values of the capacitors using a differential method. Besides, the two capacitors have to be identical. This makes an accurate determination very difficult and inefficient. In this work, we introduce a new method that can accurately and efficiently characterize the ESR, ESL, and capacitance of a high-voltage capacitor in a single discharge test employing only one capacitor and a spark gap. The electrical characterization is obtained by fitting the voltage drop across the capacitor and the current flowing through the spark gap during the discharge with simple circuit equations using a multiple linear regression method. Furthermore, the experiments have also been modeled more completely with PSpice simulations, resulting in good agreement and providing better understanding. It is found that the ESR, ESL, and capacitance obtained from the proposed methodology are consistent with the PSpice predictions, within differences of 5.71%, 4%, and 0.92%, respectively, in the demonstrated experiments.